Clot Formation in the Sipunculid Worm Themiste petricola: A Haemostatic and Immune Cellular Response - Tomás Lombardo; Guillermo A. Blanco (International Journal of Cell Biology)
Clot formation in the sipunculid Themiste petricola, a coelomate nonsegmented marine worm without a circulatory system, is a cellular response that creates a haemostatic mass upon activation with sea water. The mass with sealing properties is brought about by homotypic aggregation of granular leukocytes present in the coelomic fluid that undergo a rapid process of fusion and cell death forming a homogenous clot or mass. The clot structure appears to be stabilized by abundant F-actin that creates a fibrous scaffold retaining cell-derived components. Since preservation of fluid within the coelom is vital for the worm, clotting contributes to rapidly seal the body wall and entrap pathogens upon injury, creating a matrix where wound healing can take place in a second stage. During formation of the clot, microbes or small particles are entrapped. Phagocytosis of self and non-self particles shed from the clot occurs at the clot neighbourhood, demonstrating that clotting is the initial phase of a well-orchestrated dual haemostatic and immune cellular response.